Permanent education strategy to older adult oral health - Fidela Reyes Obediente; Evelio F. Machado Ramírez (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2020)
This article discourses about a problem present in the Integral Health Centers of Camagüey city, where a significant number of elderly people with oral diseases have been detected and for whom preventive care is needed in addition to the care provided to them, to achieve self-care in a responsible manner and with the support of the family. The objective of the present work is to expose the strategy of permanent education in oral health for the older adultthat was elaboratedwith the use of the methods and techniques of pedagogical research. A process of empirical-theoretical immersion denoted its usefulness as part of the training processes with people of these ages from the health field.